Prevention and Treatment of Venous Thromboembolism Associated with Coronavirus Disease 2019 Infection: A Consensus Statement before Guidelines - Zhai, Zhenguo; Li, Chenghong; Chen, Yaolong; Gerotziafas, Grigorios; Zhang, Zhenlu; Wan, Jun; Liu, Peng; Elalamy, Ismaïl; Wang, Chen; On behalf of the Prevention Treatment of VTE Associated with COVID-19 Infection Consensus Statement Group; Pulmonary Embolism Pulmonary Vascular Diseases Group of the Chinese Thoracic Society; Pulmonary Embolism Pulmonary Vascular Disease Working Committee of Chinese Association of Chest Physicians; National Cooperation Group on Prevention Treatment of Pulmonary Embolism Pulmonary Vascular Disease; National Program Office for Prevention Treatment of Pulmonary Embolism Deep Vein Thrombosis; China Grade Center; Evidence-based Medicine Center of School of Basic Medical Sciences of Lanzhou University (Thrombosis and Haemostasis, 2020)
Coronavirus disease 2019 (COVID-19) has caused a global pandemic in just a few months, causing millions infected. Nearly 20% of COVID-19 patients present severe coagulation abnormalities, which may occur in almost all of the severe and critical ill COVID-19 cases. Concomitant venous thromboembolism (VTE), a potential cause of unexplained deaths, has been frequently reported in COVID-19 cases, but its management is still challenging due to the complexity between antithrombotic therapy and coagulation disorders. Based on frontline practical experience and comprehensive literature review, here a panel of experts and physicians from China and Europe developed an evidence and opinion-based consensus on the prophylaxis and management of VTE associated with COVID-19. This statement aims for clinicians treating COVID-19 and provides practical recommendations in detailed situations, for example, how to choose thromboprophylactic measures for patients with diverse severity of disease and bleeding risk, or which kind of anticoagulant should be prescribed. With limited experience on COVID19-associated VTE, this expert consensus statement should be helpful for clinicians worldwide with specific suggestions.
Keywords: COVID-19; venous thromboembolism; coagulation abnormalities; prophylaxis; consensus